The Art of Defense Diplomacy: How New Forms of Diplomacy are Shaping International Relations - Khadafi, Bintang Ramadhan Yusuf; Salahudin, Salahudin; Yumitro, Gonda (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2023)
Defense diplomacy has further developed into a new form of diplomacy in international relations, which is supported by various forms of technology and also the development of social media. This research study aims to explore how this new form of diplomacy shapes international relations more broadly, as well as to determine whether defense diplomacy effectively promotes cooperation and stability among states in the context of security and defense. Then find the challenges and opportunities of defense diplomacy in the modern era. The research used mixed methods research by analyzing 244 scientific articles based on the Scopus database, Google Scholar, and Web of Science. In addition, this research also analyzed the data obtained from the VOSviewer tool. This study reveals that defense diplomacy has emerged in various forms of diplomacy, also defense diplomacy affects interactions of international relations and influences the construction of norms, identities, and interests in the international system. In terms of norms, defense diplomacy can help promote international norms related to security and defense, such as human rights and international law. In terms of identity, defense diplomacy can shape national identity in terms of defense and security. In terms of interests, defense diplomacy can influence national interests and security through cooperation in defense and reaching regional and international security agreements. Defense diplomacy brings changes in the form of building cooperation, reducing tensions, improving defense capabilities, and promoting human rights principles and international law. Through defense diplomacy, countries can strengthen international cooperation in security and defense and build strong relationships between countries. In the long run, this can help reduce tensions between countries and promote stability around the world.